Young Adults And Online Dating In Malaysia: An Exploratory Study - Ong, Grace (2019)
Youths in Malaysia today believe that online dating applications is the most conducive way to meet someone new. This study seeks to examine how Malaysians use online dating sites for actual dating purposes and the extent of self-disclosure to provide a clearer understanding of communication and possibly romantic or unromantic attachments, especially for the people within the region of Klang Valley, Malaysia. The Uses and Gratifications Theory (U&G) holds major assumptions that individuals are active, rational and objective, to the extent of being almost goal-oriented in their choices. Supplemented by SPT focusing on the importance of amount of self-disclosure for success in online dating, forms the basis of this qualitative research. The study which is conducted with 21 in-depth, semi-structured interviews that are gathered via convenience and snowball sampling and guided by the concept of data saturation found that the study of online dating behaviour has the potential to help us understand how computer mediated communication but can also provide new insights into existing interpersonal communication theories focusing on face to face relationship formation, self-presentation, and selfdisclosure.